Additional challenges in reaching hepatitis C elimination goals in Germany due to the COVID-19 pandemic - descriptive analysis of drug prescription data from January 2018 to June 2021 - Meyer, Emily D.; Dudareva, Sandra; Kollan, Christian; Mauss, Stefan; Wedemeyer, Heiner; Schmidt, Daniel; Zimmermann, Ruth (Frontiers in Public Health, 2023)
Effectively treating hepatitis C viral (HCV) infections prevents sequelae and onward transmission. In Germany, HCV drug prescriptions have declined since 2015. During the COVID-19 pandemic, lockdowns impacted the access to HCV care services and HCV treatment. We assessed if the COVID-19 pandemic further decreased treatment prescriptions in Germany. We built log-linear models with monthly HCV drug prescription data from pharmacies from January 2018 - February 2020 (pre-pandemic) to calculate expected prescriptions for March 2020-June 2021 and different pandemic phases We calculated monthly prescription trends per pandemic phase using log-linear models. Further, we scanned all data for breakpoints. We stratified all data by geographic region and clinical settings. The number of DAA prescriptions in 2020 (n=16,496, -21%) fell below those of 2019 (n=20,864) and 2018 (n=24,947), continuing the declining trend from previous years. The drop in prescriptions was stronger from 2019 to 2020 (-21%) than from 2018 to 2020 (-16%). Observed prescriptions met predictions from March 2020 to June 2021, but not during the first COVID-19 wave (March 2020-May 2020). Prescriptions increased during summer 2020 (June 2020-September 2020) and fell below the pre-pandemic numbers during the following pandemic waves (October 2020 – February 2021 and March 2021 – June 2021). Breakpoints during the first wave indicate that prescriptions plummeted overall, in all clinical settings and in four of six geographic regions. Both, outpatient clinics and private practices prescribed overall as predicted. However, outpatient hospital clinics prescribed 17-39% less than predicted during the first pandemic wave. HCV treatment prescriptions declined but stayed within the lower realms of predicted counts. The strongest decline during the first pandemic wave indicates a temporary HCV treatment gap. Later, prescriptions matched predictions despite of pronounced decreases during the second and third waves. In future pandemics, clinics and private practices need to adapt more rapidly to maintain a continuous access to care. In addition, political strategies should focus more on continuously providing essential medical care during periods of restricted access due to infectious disease outbreaks. The observed decrease in HCV treatment may challenge reaching the HCV elimination goals in Germany by 2030.